Interventions for promoting physical activity in people with newly diagnosed Parkinson’s disease: scoping review - Jonathan Gilby; Bridie Kent; Rachel Knight Lozano; Jonathan Marsden (Systematic Reviews)
Abstract Background There is increasing evidence to suggest that physical activity can slow Parkinson’s progression. There is also increasing interest in non-pharmacological interventions to alleviate Parkinson’s symptoms. This scoping review aimed to map and describe the evidence for interventions that promote physical activity in people with newly diagnosed Parkinson’s. Methods Studies conducted since 2011, on adults with Parkinson’s (≥ 18 years), investigating the effects of non-pharmacological interventions to promote physical activity and/or exercise were considered. Interventions needed to be conducted in healthcare or healthcare-related settings for people within 5 years of Parkinson’s diagnosis. Published or unpublished full-text articles since 2011 were searched in November 2023, using online focused, broad, and grey literature databases. JBI scoping review methodology was used and results presented in table format accompanied by a narrative review. Results A total of 22 articles with a variety of research designs were included with 14 randomized trials, one single-site, prospective, single-arm study, two retrospective cohort studies, one case series, two case reports, and two qualitative reports. Many studies (n = 7) were conducted in outpatient clinics with the majority of interventions (n = 17) involving physiotherapists. Interventions varied widely, including aerobic exercise, balance exercise, dance, and yoga. The duration of intervention varied from 4 weeks to 8 years. Dosage of interventions varied widely from 30 to 90 min, and from twice weekly to seven times weekly. Several different outcome measures related to physical activity levels and/or physical fitness were used. The most frequent clinician/researcher reported outcome measure was the 6-min walk test (in nine studies) and the most frequently used participant/patient reported outcome measure was the 39-item Parkinson’s Disease Questionnaire (PDQ-39) (also in nine studies). The review showed limited research in identifiable cohorts with newly diagnosed Parkinson’s. Sample sizes were predominantly small. In all but one study, authors interpreted their results as favoring interventions to promote physical activity for people with newly diagnosed Parkinson’s. All authors recommended further studies. Conclusions There is a need for more research with larger sample sizes and standardized reporting to inform the evidence base for interventions that promote physical activity in people with newly diagnosed Parkinson’s. Systematic review registration https://pearl.plymouth.ac.uk/ ( http://hdl.handle.net/10026.1/20098 )